The impact of incentives on job satisfaction: A field study on Al-Jamaaz Group Company in Riyadh - Al-Maslokhi, Yousef Obaid (Journal of Economic, Administrative and Legal Sciences, 2024)
The study aimed to identify the impact of incentives on job satisfaction among employees, this objective, which were: knowing the reality of the application of both material and moral incentives at Al-Jamaaz Group Company, in addition to knowing the level of job satisfaction among employees. To achieve these objectives, the descriptive analytical approach was used. In order to collect the necessary data to achieve the objectives, a random sample of (200) employees from the Al-Jamaaz Group Company in Riyadh, Saudi Arabia, was selected. A questionnaire prepared by the researcher consisting of (62) item was applied to them, and its validity and reliability were verified. After that, the data was processed using the (SPSS) program. Accordingly, the study reached a number of results, the most important of which are: The degree of availability of the application of both material and moral incentives in the company was high, whether for the total degree of both or at level of each item separately. The results also showed a high level of job satisfaction among employees. The results also indicated a positive and statistically significant effect of both material and moral incentives on the level of job satisfaction.